Tecnologia, mobilidade e dispersão metropolitana : Sistema Anhanguera / Bandeirantes - Eigenheer, Daniela Maria (2011)
The changes of population displacement and distribution and their activities over the territory due to productive changes and technological advances with emphasis on the transportation and communication sectors, changes the mobility and the dynamic of land use and occupation, restructuring and directing the cities evolution and expansion. Within this context, this research pointed out the transformations in the urban growth of São Paulo Vector northwest, formed by the Anhanguera/Bandeirantes System, the main connection axis between the two largest and richest metropolitan areas in the state, Sao Paulo and Campinas, on which it structure and consolidated the formation of a global macro region. By understanding the evolution of socio-spatial dynamics of the two regions (São Paulo and Campinas), connected by Anhanguera/ Bandeirantes System, aims to understand the logic of this territorial occupation of regional urban mobility, which is related to new production structures and that is impacted by the new contemporary metropolis territorial organization, with new limits. It aims to identify the changes that occur in this major road infrastructure, and them to help formulating urban and regional public policies, able to effectively integrate new areas of urban sprawl to its metropolitan context, ensuring a balanced development